PT HARITA GROUP’S INVESTMENT AND ITS IMPLICATIONS FOR THE WELFARE OF THE OBI ISLAND COMMUNITY, SOUTH HALMAHERA - Fandy Yones Latuni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to measure the satisfaction level of the community in Pulau Obi regarding the investment from PT Harita Group in the mining sector. The research employed a descriptive survey method by collecting primary data through questionnaires distributed to 100 respondents in Pulau Obi. Data analysis was conducted using the Servqual method to assess the gap between the perceived implementation and the expected importance of investment aspects as experienced by the community. Additionally, the Importance-Performance Analysis (IPA) was used to map priority areas for service improvement based on community responses. The results show that most items had a negative gap value, indicating that the implementation of the investment has not fully met community expectations, especially in the areas of household income allocation for consumption and housing conditions. However, aspects related to education and healthcare services have relatively high performance and importance and should be maintained. The IPA results divided the attributes into four quadrants, highlighting income and housing as areas needing urgent improvement, while education and healthcare services were areas to be sustained. In conclusion, to enhance community welfare in Pulau Obi, it is crucial to focus on improving economic conditions and housing quality without neglecting the maintenance of existing satisfactory educational and health services. This study provides essential insights for PT Harita Group and stakeholders to develop more inclusive, sustainable investment strategies that benefit the local community and contribute to long-term regional development.